Evaluation of Accountability of Accounting and Financial Reporting System in Islamic Republic of Iran - Jafar Babajani (مطالعات تجربی حسابداری مالی, 2004)
In a democratic society, Power ultimately rests in the hands of the citizen ry. The citizens delegate that power to public officials through the election process.In such society accountability requires government to answer the citizenry - to justify the raising of public resources and the purposes of which they are used.Govern mental accountability is based on the belief that the citizenry  has  a " right  to  know", a  right  to  receive   only declared facts that may lead to public debate by the citizens and their elected representatives. Accounting and financial reporting plays a major role in fulfilling government's duty to be publicly accountable in the democratic society (GASB, 1993). The main purpose of this research is assessing accountability of governmental accounting and financial reporting system of Islamic Republic of Iran. In accordance to that purpose this research 1s divided to three stages as described below: